No beneficial use of the wearable cardioverter defibrillator among patients suffering from inherited and congenital heart disease: data from a European multicenter registry - Koepsel, Katharina; Dreher, Tobias C.; Blockhaus, Christian; Gotzmann, Michael; Klein, Norbert; Kuntz, Thomas; Shin, Dong-In; Lapp, Hendrik; Schiedat, Fabian; Abumayyaleh, Mohammad S. A.; Beiert, Thomas; Weth, Christian; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Data on the use of the wearable cardioverter defibrillator in patients suffering from inherited and congenital heart disease are limited. Consequently, evidence for guideline recommendations in this patient population is lacking. Methods: In total 1,675 patients were included in a multicenter registry of eight European centers. In the present cohort, we included 18 patients suffering from congenital and inherited heart disease. Results: Nine patients (50%) were male with a mean age of 41.3 ± 16.4 years. Four patients suffered from hypertrophic cardiomyopathy (HCM), four patients suffered from non-compaction cardiomyopathy (NCCM), two patients were diagnosed with arrhythmogenic right ventricular cardiomyopathy (ARVC) and one patient suffered from muscular dystrophy of the limb-girdle type with cardiac involvement, secondary cardiomyopathy. Three patients presented with Brugada syndrome (BrS). One patient suffered from long-QT syndrome type 1 (LQTS1). Furthermore, two patients had congenital heart defects and one patient suffered from cardiac sarcoidosis (CS). There were no appropriate/inappropriate shocks with the WCD in this cohort. One patient had recurrent self-limiting sustained ventricular tachycardia during the wear time, but actively inhibited a shock and was hospitalized. The compliance rate in this cohort was 77.8% with a mean wear time of 45.3 ± 26.9 days with a mean follow-up time of 570 ± 734 days. 55.6% (10/18) of the patients received an ICD after WCD wear time. Conclusions: This retrospective study of patients with inherited and congenital heart disease shows that WCD use is not beneficial in the majority of patients with inherited and congenital heart disease.